Convergent adaptation of cellular machineries in the evolution of large body masses and long life spans - Croco, Eleonora (Biogerontology, 2017)
In evolutionary terms, life on the planet has taken the form of independently living cells for the majority of time. In comparison, the mammalian radiation is a relatively recent event. The common mammalian ancestor was probably small and short-lived. The “recent” acquisition of an extended longevity and large body mass of some species of mammals present on the earth today suggests the possibility that similar cellular mechanisms have been influenced by the forces of natural selection to create a convergent evolution of longevity. Many cellular mechanisms are potentially relevant for extending longevity; in this assay, we review the literature focusing primarily on two cellular features: (1) the capacity for extensive cellular proliferation of differentiated cells, while maintaining genome stability; and (2) the capacity to detect DNA damage. We have observed that longevity and body mass are both positively linked to these cellular mechanisms and then used statistical tools to evaluate their relative importance. Our analysis suggest that the capacity for extensive cellular proliferation while maintaining sufficient genome stability, correlates to species body mass while the capacity to correctly identify the presence of DNA damage seems more an attribute of long-lived species. Finally, our data are in support of the idea that a slower development, allowing for better DNA damage detection and handling, should associate with longer life span.